Analysis of Factors Influencing Career Adaptability of Application-Oriented Undergraduate Students with Variable Career Orientation - Lu, Yi; Yang , Binfeng (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: This study aims to explore the influencing factors of the development status of application-oriented undergraduate students in terms of variable career orientation, career self-efficacy, and career adaptability. Through this study, we aim to guide college students to help them establish a positive career attitude in order to maintain resilience and confidence throughout their career development. At the same time, this study aims to enhance college students' awareness of the importance of career development and strengthen their understanding of individuals and their environment, to more effectively grasp the trajectory of their career development. Materials and Methods: This study used the Variable Career Orientation Scale, Career Self-Efficacy Scale, and Career Adaptability Scale for investigation. A total of 1,022 students from four applied undergraduate institutions in Henan Province, China, participated in the survey. SPSS 27.0 statistical software was used for statistical analysis of the data, including independent sample t-test, ANOVA, Pearson correlation analysis, and regression analysis. Results: Research has found that the variable career orientation of Chinese applied undergraduate students has a significant positive impact on their career adaptability; Chinese applied undergraduate students' career self-efficacy has a significant positive effect on career adaptation; Chinese applied undergraduate students' career self-efficacy mediates the relationship between variable career orientation and career adaptability. Career self-efficacy partially mediates the relationship between variable career orientation and career adaptability. Conclusion: This study clarifies that Chinese applied undergraduate students' variable career orientation and career self-efficacy have a significant positive effect on their career adaptability, and career self-efficacy plays a mediating role in this process. Universities should cultivate students' active and adaptable career direction through courses, practices, and other means, carry out training to enhance their career self-efficacy, help students improve their career adaptability, and seize opportunities for career development.